2022
DOI: 10.1007/s00423-022-02495-8
|View full text |Cite
|
Sign up to set email alerts
|

When to operate after SARS-CoV-2 infection? A review on the recent consensus recommendation of the DGC/BDC and the DGAI/BDA

Abstract: Since the eruption of the worldwide SARS-CoV-2 pandemic in late 2019/early 2020, multiple elective surgical interventions were postponed. Through pandemic measures, elective operation capacities were reduced in favour of intensive care treatment for critically ill SARS-CoV-2 patients. Although intermittent low-incidence infection rates allowed an increase in elective surgery, surgeons have to include long-term pulmonary and extrapulmonary complications of SARS-CoV-2 infections (especially “Long Covid”) in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 130 publications
(163 reference statements)
1
11
0
Order By: Relevance
“…Global or local lockdown policies and recommendations regarding postponement of elective therapies during the last two pandemic years aim at providing necessary health care capacities especially during wave-like outbreaks of different variants of SARS-CoV-2. Therefore, the discussion behind postponements of elective surgical therapies is primarily to hold up bed, intensive care as well as operating room capacities available during the pandemic and secondarily to preserve patients and medical staff from nosocomial infection with SARS-CoV-2 [1][2][3][4]. However, postponement of elective surgical therapies might not be detrimental in the short-term follow-up upon diagnosis, but delayed treatments might have some harmful effects beyond that short range in the longer-term outcome [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global or local lockdown policies and recommendations regarding postponement of elective therapies during the last two pandemic years aim at providing necessary health care capacities especially during wave-like outbreaks of different variants of SARS-CoV-2. Therefore, the discussion behind postponements of elective surgical therapies is primarily to hold up bed, intensive care as well as operating room capacities available during the pandemic and secondarily to preserve patients and medical staff from nosocomial infection with SARS-CoV-2 [1][2][3][4]. However, postponement of elective surgical therapies might not be detrimental in the short-term follow-up upon diagnosis, but delayed treatments might have some harmful effects beyond that short range in the longer-term outcome [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since the rapid spread of the SARS-CoV-2 around the world in late 2019, a high amount of research had been published regarding the pandemic, the characteristics of the virus and treatment modalities of COVID-19, which are urgently needed [4]. However, the literature reveals some evidence about dramatic negative effects of the pandemic on various medical fields and health care services, e.g., in oncology, cardiovascular diseases, etc., as well as on the outcome of respective patients [5,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…15 A recent review identified 10 studies that looked at surgical outcomes in patients with perioperative SARS CoV2 infection. 16 However, the studies were heterogeneous (different countries, retrospective vs.…”
Section: Discussionmentioning
confidence: 99%
“…prospective, inclusion of patients with pre and postoperative infection, variable techniques of testing for COVID-19, small sample sizes, elective and emergency procedures and surgeries of varying complexity) making the interpretation of their results difficult. 16 Surgery for cancer (solid tumors) is a key treatment modality, is often complex and may be associated with significant perioperative morbidity. Oncological surgery is considered semi-urgent since any delays could result in progression of cancer, potentially rendering the patient inoperable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation